Direct Catalyst‐Free Chemical Vapor Deposition of ZnO Nanowire Array UV Photodetectors with Enhanced Photoresponse Speed1 . Issue 8 (20th April 2017) - Zhan, Zhaoyao; Xu, Liping; An, Jianing; Du, Hejun; Weng, Zhankun; Lu, Wenqiang
Abstract : ZnO‐based photodetectors (PDs) have long response times at magnitude of tens to hundreds of seconds, hampering their practical UV detection. The slow oxygen chemisorption/desorption process is the main cause of the slow response of UV PDs based on single ZnO nanowires (NWs). Here, the authors find the response speed of ZnO NW‐based UV PDs could be improved by directly fabricating UV PDs on entangled ZnO NW array grown on SiO2 through a catalyst‐free chemical vapor deposition (CVD) process. Specifically, the interconnections in ZnO NW array creates NW–NW junction barriers, which dominate the inter‐wire charge transport. The switching of UV illumination induces fast tuning of NW–NW junction barrier height, which contributes to the enhanced response speed of the ZnO NW array UV PDs. Abstract : Carrier generation and transport in ZnO NW array PD. The extra Nanowire–Nanowire junction barriers dominate charge transport in the ZnO NW array; the electrons must overcome the junction barriers to transport from one NW to another. Under UV illumination, the height of junction barriers is much reduced, and thus conductivity of ZnO NW array is greatly enhanced.